Quality of the exotic parasitoid cotesia flavipes (Hymenoptera: Braconidae) does not show deleterious effects after inbreeding for 10 generations - Trevisan, Maíra [UNESP]; De Bortoli, Sergio A. [UNESP]; Vacari, Alessandra M. [UNESP]; Laurentis, Valéria L. [UNESP]; Ramalho, Dagmara G. (Public Library of Science (PLoS), 2016)
Although the parasitoid Cotesia flavipes (Cameron) has proven effective in controlling sugarcane borer Diatraea saccharalis (Fabricius) for many years, concern has arisen over the quality of individuals produced at large scales. The parasitoid has been reared in laboratories in Brazil for more than 40 years, with no new introductions of new populations during that period. Since the quality of the parasitoids was not verified at the time of the species' introduction in Brazil, we do not know if there has been any reduction in quality so far. However, it is possible to determine whether the parasitoid could reduce in quality in future generations. Thus, the objective of this research was to assess the quality of these insects over 10 generations and look for evidence of any loss in quality. We used two populations: one from a biofactory that has been maintained in the laboratory for over 40 years, and an inbred laboratory population. Both were bred, and compared for 10 generations. We wanted to determine what happened to the quality of the parasitoid after 10 generations in an extreme inbreeding situation. To assure inbreeding, newly emerged females were forced to mate with a sibling. Individual females were then allowed to parasitize larvae of D. saccharalis. We performed evaluations for each generation until the tenth generation, and recorded the sex ratio, percentage emergence, number of offspring/females, and longevity of both males and females. Results of the measurements of biological characteristics demonstrated random significant differences between populations; best results were obtained intermittently for both the biofactory population and the inbred population. No significant differences across generations for the same population were observed. Thus, rearing of a C. flavipes population subjected to inbreeding for 10 generations was not sufficient to reveal any deleterious effects of inbreeding.